Epigenetic analysis confirms no accelerated brain aging in schizophrenia - Voisey, Joanne (NPJ Schizophr, 2017)
Epigenetic aging is associated with several biological mechanisms and diseases. We assessed two brain data sets, one small (n = 48) and one large (n = 392), to test epigenetic aging in schizophrenia. DNA methylation age from frontal cortex was significantly correlated with chronological age but no significant differences in DNA methylation age acceleration between schizophrenia cases and controls were observed in both data sets. Our results were consistent with a previous study investigating schizophrenia and epigenetic aging in superior temporal gyrus. Future studies targeting different brain regions and defined cell types are warranted to further investigate accelerated brain aging in schizophrenia.